A retrospective cohort study of the application of Santulli enterostomy in neonatal necrotizing enterocolitis - Zhe Fu; Jingmin Zhang; Fanyue Qin; Xinru Wang; Hua Huang; Hongwei Huang; Mingjun Zheng; Peng Wang; Weibo Zhang; Hongguang Shi (Scientific Reports)
Abstract The use of Santulli enterostomy (SE) for necrotizing enterocolitis (NEC) has been limited to a small number of studies involving a small number of patients and no control group. Our study aimed to compare the clinical safety and efficacy of Santulli enterostomy with those of single- or double-lumen enterostomy for neonatal NEC through a retrospective cohort study. One hundred ten patients who met the criteria were divided into an SE group (64 patients) and a conventional enterostomy (CE) group (46 patients). The CE group underwent single- or double-lumen enterostomy. There were no significant differences in complication rates or prognoses between the two groups after either procedure. Although the stoma was positioned higher in the SE group, the length of the unused small intestine (USI) was not significantly different. Multivariate analysis revealed that the length of the USI influenced the likelihood of malnutrition after enterostomy (OR = 1.108, P = 0.008). After stoma closure, compared with those in the CE group, the operation time, intestinal recovery time, fasting time, hospitalization time, intraoperative blood loss volume and the incidence of complications requiring surgical reintervention was significantly lower in the SE group. In conclusion, Santulli enterostomy is not only a safe treatment option for NEC but also an effective method for increasing the length of the small intestine after enterostomy, thereby improving the patient’s postoperative nutritional status. In addition, the procedure is associated with good recovery and a reduced incidence of surgical reintervention after stoma closure.